Tumor cell-derived ISG15 promotes fibroblast recruitment in oral squamous cell carcinoma via CD11a-dependent glycolytic reprogramming - Wang, Ssu-Han; Chen, Yu-Lin; Huang, Shih-Han; Fu, Yu-Ke; Lin, Su-Fang; Jiang, Shih Sheng; Liu, Shu-Chen; Hsiao, Jenn-Ren; Chang, Jang-Yang; Chen, Ya-Wen (Oncogenesis (New York, NY), 2025)
Cancer-associated fibroblast (CAF) recruitment and activation within the tumor microenvironment (TME) are increasingly acknowledged as drivers of oral squamous cell carcinoma (OSCC) tumor growth and metastasis. Therefore, the mechanisms underlying tumor cell and fibroblast crosstalk warrant further investigation. We discovered that ectopic interferon-stimulated gene 15 (ISG15) expression, which is a promising and novel oncoprotein biomarker elevated in a variety of cancers, enhanced OSCC growth and elevated collagen and α-smooth muscle actin (α-SMA) expression in ISG15-expressing tumors. Analysis of immunohistochemistry revealed high ISG15 expression in human oral tissues correlated with high expression of α-SMA and fibroblast activation protein (FAP). Fibroblast migration and recruitment by ISG15-expressing OSCC cells were confirmed by in vitro and in vivo experiments. Exogenous ISG15 induced fibroblast migration, morphological changes, and vimentin expression. Enrichment of glycolysis pathway genes, as well as increased glycolysis-related gene expression, glucose uptake, and lactate production were observed in ISG15-treated fibroblasts. Lactate release and fibroblast migration were blocked by a competitive inhibitor of glucose metabolism. Furthermore, the knockdown of integrin αL (ITGAL)/CD11a, a subunit of ISG15 receptor lymphocyte functional-associated antigen-1 (LFA-1), in immortalized fibroblasts diminished extracellular ISG15-mediated glycolysis and migration. Our findings suggest that ISG15 derived from OSCC cells interacts with fibroblasts through the LFA-1 receptor, leading to glycolytic reprogramming and promotion of fibroblast migration into the TME.